Frequency and Severity of Vitamin D Deficiency among Vitiligo Patients in Karachi - Rafique, Rabia; Bukhari, Sadaf; Junaid, Shakila; Malik, Tooba; Zameer, Farina; Neeta Maheshwary (Journal of Pakistan Association of Dermatologists, 2025)
Background: Depigmented macules of various shapes are a hallmark of vitiligo, an autoimmune condition brought on by the destruction of melanocytes in the skin. All skin types and both sexes may be affected by the condition, which has been linked to other systemic autoimmune disorders such scleroderma, lupus erythe-matosus, alopecia areata and autoimmune thyroiditis. Objectives: The aim of this study was to assess the frequency and severity of vitamin D deficiency among patients diagnosed with vitiligo. Methods: This Cross-Sectional study was conducted in the Department of Dermatology Pakistan Navy Station (PNS) Shifa Hospital, Karachi for six months from June 2018 to December 2018. Patients with a clinical diagnosis of vitiligo were enrolled in the study following strict adherence to the defined inclusion and exclusion criteria. A predesigned questionnaire documented demographic factors such age, name, disease duration and gender. These patients’ blood samples were obtained the same day and sent to the pathology lab of PNS Shifa hospital, Karachi to determine their vitamin D levels by radioimmunoassay. Vitamin D levels were docu-mented using a predesigned proforma on the day of reporting. Results: The patients mean age was 33 ± 19.36 years. A total of 124 patients were included in the study. Among them, 52 (42%) were male and 72 (58%) were female. Vitamin D deficiency was observed in 91 (73%) patients, while 33 (27%) patients had sufficient vitamin D levels. Conclusion: Vitamin D deficiency was highly prevalent among patients with vitiligo, highlighting the need for routine screening and potential correction as part of comprehensive management strategies.